1993
DOI: 10.1084/jem.178.2.449
|View full text |Cite
|
Sign up to set email alerts
|

PECAM-1 is required for transendothelial migration of leukocytes.

Abstract: SummaryPlatelet/endothelial cell adhesion molecule 1 (PECAM-1; CD31) is crucial to the process of leukocyte transmigration through intercellular junctions of vascular endothelial cells. A monoclonal antibody to PECAM, or recombinant soluble PECAM, blocks transendothelial migration of monocytes by 70-90%. Pretreating either the monocytes or the endothelial junctions with antibody blocks transmigration. If the endothelium is first activated by cytokines, anti-PECAM antibody or soluble recombinant PECAM again blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
739
1
10

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,029 publications
(790 citation statements)
references
References 51 publications
40
739
1
10
Order By: Relevance
“…First, a report by Oda and Katori (61) (using the model of leukocyte flow in a hamster cheek pouch) suggested that glucocorticoids did not affect leukocyte rolling or firm adhesion to the endothelium, but rather, they affected the later stages of transmigration, which are at least partially mediated by PECAM (11). Second, interfering with PECAM function inhibits neutrophil trafficking in animal models of inflammation (11,62). Third, TNFa treatment has been reported to cause redistribution of PECAM on vascular endothelium to intercellular junctions (19), and we had previously found reduced TNFa levels after MP treatment (35).…”
Section: Discussionmentioning
confidence: 99%
“…First, a report by Oda and Katori (61) (using the model of leukocyte flow in a hamster cheek pouch) suggested that glucocorticoids did not affect leukocyte rolling or firm adhesion to the endothelium, but rather, they affected the later stages of transmigration, which are at least partially mediated by PECAM (11). Second, interfering with PECAM function inhibits neutrophil trafficking in animal models of inflammation (11,62). Third, TNFa treatment has been reported to cause redistribution of PECAM on vascular endothelium to intercellular junctions (19), and we had previously found reduced TNFa levels after MP treatment (35).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-PECAM blocking reagents have been demonstrated to block the transmigration of monocytes (14), neutrophils (14, 18 -20), NK cells (21), and eosinophils (22). A recent study using an in vitro model of inflammation described the involvement of CD99, a heavily glycosylated 32-kDa transmembrane protein, as a second molecule in the transmigration of monocytes across EC borders (23).…”
Section: Cd99 Is a Keymentioning
confidence: 99%
“…Platelet endothelial cell adhesion (PECAM-1) is of the immunoglobulin (Ig)-superfamily with wide variety of functions in platelet activation, inflammation, cell survival and the immune response and involved in transendothelial migration of monocytes (TEM) [1][2][3][4]. Thus it has a role in atherosclerotic plaque formation.…”
Section: Introductionmentioning
confidence: 99%
“…It has 6 Ig-like extracellular domains (encoded by exon 3-8) a short trans-membrane domain (encoded by exon 9) and a short cytoplasmic tail (encoded by exon [10][11][12][13][14][15][16] [6,7]. The importance of the first domain of PECAM-1 (encoded by exon 3) is underscored since PECAM-1 forms homophilic binding via its 1st or 1st plus 2nd extracellular Ig-like domains or heterophilic binding with other molecules to mediate cell-cell adhesion [3,8]. A Mutation in PECAM-1 gene in Exon-3 has been identified that involves a base pair substitution (C?G) at position ?373 causing Leucine (Leu) to Valine (Val) substitution at amino acid position 125 (rs668) [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation